Impact of holding home stimulant(s) on agitation in a child and adolescent inpatient psychiatric population - Anupha M. Mathew, PharmD, BCPS; Sophie Robert, BPharm, PharmD, BCPP; Clint Ross, PharmD, BCPP; Erin Weeda, PharmD, BCPS; Adrienne Pruitt, MD (American Association of Psychiatric Pharmacists, 2023)
Introduction: This study aimed to compare the rates of agitation-related interventions associated with initial holding versus continuation of home stimulant(s) in a child and adolescent population at the time of admission to an inpatient psychiatric facility. Methods: This retrospective chart review included patients less than 18 years of age who were admitted to an academic medical center between July 1, 2017, and July 1, 2018. Patients were divided into 2 groups: those continued on their home stimulant(s) and those who had them held. We compared both groups on agitation-related outcomes by examining the difference in the number of level I or II events or as-needed medication administrations. Mechanical restraints and closed-door seclusions were grouped as level I events, and level II events consisted of nonmechanical restraint. Results: The analysis included 169 patients. In total, 126 (75%) patients were continued on their home stimulant, and 43 (25%) had them held. The occurrence of the composite endpoint of level I or II events or as-needed intramuscular medication administration was numerically higher in the group that had their home stimulant held (27.9% vs 23%; P =.52). Level I events were also numerically higher but not statistically significant in the group that had their home stimulant held (16.3% vs 11.9%; P = .46). Discussion: The composite outcome of as-needed intramuscular medication administration and level I or II events was numerically higher in the group that had their home stimulant held. Use of a larger sample size and adjusted analyses may help elucidate covariates that impact agitation-related outcomes.